Structure-function of recombinant Na/H exchanger regulatory factor (NHE-RF). - Weinman, E J (1998)
Inhibition of the renal brush border membrane (BBM) Na/H exchanger by cAMP-dependent protein kinase, PKA, requires participation of a recently cloned regulatory cofactor, Na/H exchanger-regulatory factor (NHE-RF). As deduced from the cDNA of this 358-amino acid protein, amino acids 11-101 and amino acids 150-241 of the NHE-RF protein share 74% overall homology suggesting duplication of these PDZ containing domains. The serine residues at amino acid position 289 and 340 are considered to be the most likely sites for PKA mediated phosphorylation. To study the structure- function relation between NHE-RF and PKA mediated inhibition of the rabbit BBM Na/H exchanger, the effect of recombinant proteins representing full-length NHE-RF as well as truncated and mutant forms of NHE-RF were determined using a reconstitution assay. The reconstitution assay employed a fraction of rabbit BBM proteins that contains Na/H exchanger activity that is not regulated by PKA. NHE-RF in the presence of ATP and Mg but not PKA, inhibited Na/H exchange activity in a concentration-dependent manner. In the presence of PKA, there was a significant left shift in the dose-response relation such that 10(-12) M NHE-RF inhibited Na/H exchange transport by 30% in the presence but not in the absence of PKA. A recombinant polypeptide representing amino acids 1-151 (Domain I) did not affect Na/H exchange transport in the presence or absence of PKA. A polypeptide representing amino acids 149-358 (Domain II) in the presence of ATP and Mg but not PKA, inhibited Na/H exchange activity in a concentration-dependent manner. In the presence of PKA, there was a left shift in the dose-response relation. 10(-12) M of Domain II polypeptide inhibited transport by 18% in the presence but not in the absence of PKA. Mutation of serine residues 287, 289, and 290 to alanine did not affect the inhibitory effect in the absence of PKA but abolished the left shift in the dose-response relation elicited by PKA. Mutation of serine residues 339 and 340 to alanine were without effect on PKA dependent regulation of Na/H exchange transport. These studies indicate that NHE-RF inhibits basal rabbit renal BBM Na/H exchange activity-an effect which is augmented by PKA. The amino acid sequences in the polypeptide containing only the NH2-terminal PDZ domain of NHE-RF have no intrinsic activity as an inhibitor but appears to be required for the full-length NHE-RF to express its full inhibitory effect on the BBM Na/H exchanger. One or more of the serine residues at positions 287, 289, and/or 290 represent the critical PKA phosphorylation site(s) on the NHE-RF protein that mediates the physiologic effect of cAMP on the renal BBM Na/H exchanger.